The Relationship of Birth Weight of Babies with Perineal Rupture in Normal Childbirth in RoomVK Rsia Sitti Khadidjah, Gorontalo City - Faramita Latif; Harismayanti; Ani Retni (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
A woman who gives birth to a baby weighing ?4000 grams has a higher risk of experiencing perineal rupture. This condition occurs due to pressure from the fetal head or shoulders during the delivery process. The purpose of this study was to determine the relationship between birth weight and perineal rupture during normal delivery in the VK Room of Sitti Khadidjah Hospital, Gorontalo City. This research used a quantitative method with a descriptive analytical design through a cross-sectional approach. The population consisted of all mothers experiencing perineal rupture, with a sample of 33 respondents selected using the total sampling technique. Data were collected using observation sheets and analyzed using the Chi-Square test. The results showed a significant relationship between birth weight and perineal rupture during normal delivery, with a p-value of 0.000 (<0.05). In conclusion, there is a relationship between birth weight and perineal rupture during normal delivery in the VK Room of RSIA Sitti Khadidjah, Gorontalo City. It is recommended that health workers improve their knowledge and competence in managing normal childbirth to prevent complications, including perineal rupture.